Sexual Harassment Reflected In Novel The House On Mango Street: A Feminist Perspective - Yanti, Elga Dwi; Nugroho, Abdillah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to investigate the underlying themes of sexual harassment in "The House on Mango Street" a well-known book by Sandra Cisneros. This study attempts to analyze and clarify the complex depictions of gender-based harassment in the story from a feminist perspective. In order to analyze the experiences of the female characters in the book and throw light on their interactions with sexual harassment and how it affects their lives, the research will use literary study analysis methodologies. The proposal aims to advance the conversation on gender-based violence by exploring this important topic and by offering new feminist interpretations of Cisneros's writing.